Modern requirements for the teaching of the educational course “Educational Management” in higher educational institutions - Norova Kamola Yunusovna (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2024)
The interconnectedness of the higher educational institution's content, forms, and procedures demonstrates its role in pedagogical processes and the development of future professionals for the administration of didactic processes. In the article, the researcher emphasized the need of managing the didactic process in accordance with society's overall aims and needs. This article describes how the accuracy of the content, forms, and techniques of teachers' and students' actions serves as the foundation for didactic processes.